Correlation between Smartphone Addiction Risk with Anxiety Level of Elementary Schooler in Surabaya - Aflahudin, M Ahda Naufal; Nining Febriyana; Lilik Djuari; Rizal (Jurnal Psikiatri Surabaya, 2022)
Backgound: Smartphone addiction is an individual's dependence on using a smartphone repeatedly and excessively, regardless of the negative consequences it causes. Depending on the frequency and duration of smartphone use, unwanted effects can occur, one of which is anxiety disorders. Aims: The purpose of this study was to analyze the relationship between the risk of smartphone addiction and anxiety level in elementary school children. Methods: This study used an analytic design with a cross sectional approach. The population in this study were children who owned smartphones at Khadijah Ahmad Yani Elemetary School at Surabaya in grades 5 and 6. The total sample of the study was 72 respondents from 224 students in grades 5 and 6 using consecutive sampling. The independent variable in this study is the risk of smartphone addiction and the dependent variable in this study is anxiety. The data was obtained from modified SAS-SV and ZSAS instruments, and analyzed using Spearman's correlation. Results: The results of statistical tests show the value of p = 0.001 and the value of r = 0.377 which means that there is a positive relationship between smartphone addiction and anxiety in Khadijah Ahmad Yani Elementary School Surabaya and is significant in statistics . Conclusion: Children who are at risk of smartphone addiction have a higher likelihood of experiencing anxiety.